Simulating star clusters across cosmic time: I. Initial mass function, star formation rates, and efficiencies - He, Chong-Chong; Ricotti, Massimo; Geen, Samuel Thomas (Monthly notices of the Royal Astronomical Society, 2019)
We present radiation-magneto-hydrodynamic simulations of star formation in self-gravitating, turbulent molecular clouds, modelling the formation of individual massive stars, including their UV radiation feedback.